Towards an African ecogender theology: A decolonial theological perspective - Kaunda, Chammah J (Stellenbosch Theological Journal, 2016)
The struggles for environmental and gender justice have challenged how theology is done in Africa. This article framed within the context of continuous search for life-giving African Christianity, argues that a radical relational solidarity that existed between African humanity and environment in some Zambian traditional societies was grounded on ecogender principle. Thus, it seeks to probe deeper into contemporary challenge of African men’s alienation from environment as a consequence of colonial quest to restructure African social order. Employing decolonial theological perspective, the article tried to reinterpret some life-giving elements from Bemba and Shila cultural heritage in order to re-conceptualize contemporary African Christian ecotheology. It is from this perspective where African ecogender theology is constructed towards transformation of African human and environment relationship.